The mediating effect of job burnout between workplace violence and sleep disorders among emergency department nurses - Mao, Jizhou; Gu, Zhihan; Zhong, Luying; Zhang, Hao; Chen, Xiaoli; Zou, Liqun (Frontiers in Public Health, 2025)
BackgroundSleep disorders severely impact the health of emergency department nurses and the quality of nursing care. Workplace violence is a significant contributing factor to the occurrence of sleep disorders among nurses.ObjectiveTo investigate whether job burnout plays a mediating role between workplace violence and sleep disorders among emergency nurses, and to determine the degree of interaction between workplace violence, job burnout and sleep disorders.MethodA cross-sectional survey study was conducted from December 2023 to January 2024, in which 1,540 emergency department nurses in China were surveyed using workplace violence assessment, job burnout assessment and sleep disorder assessment questionnaires. Spearman correlation analysis was employed to assess the relationships among workplace violence, job burnout, and sleep disorders. Mediation structural equation modeling analysis was performed using the PROCESS macro in SPSS which is a plug-in special for mediating and moderating effect analysis.ResultsAmong the 1,540 emergency department nurses surveyed, 59.3% experienced sleep disorders. Workplace violence showed a positive correlation with job burnout (r = 0.529, p < 0.01) and with sleep disorders (r = 0.950, p < 0.01). Job burnout was also positively correlated with sleep disorders (r = 0.343, p < 0.01). Workplace violence significantly predicted job burnout (β = 1.658, p < 0.01) and sleep disorders (β = 0.250, p < 0.01). Job burnout significantly predicted sleep disorders (β = 0.132, p < 0.01). The overall mediating effect of job burnout between workplace violence and sleep disorders accounted for 46.7% of the total effect, and this mediating effect was statistically significant.ConclusionJob burnout has mediated the impact of workplace violence on sleep disorders among emergency nurses. This indicates that intervening in job burnout among emergency department nurses is a key pathway to reducing the occurrence of their sleep disorders. Simultaneously, combining interventions targeting workplace violence may yield more comprehensive and efficient results. Future research should employ longitudinal designs to examine the impact trajectories of workplace violence on job burnout and sleep disorders among emergency nurses.